Toner

By introducing controlled volume resistivity fine particles and fatty acid metal salts into the toner particles, the problems of image drag and retransfer in the electrophotographic equipment are solved, and the durability and image quality of the equipment are improved in different environments.

CN112180697BActive Publication Date: 2024-12-24CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010632878.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-02
Filing Date
2020-07-01
Publication Date
2024-12-24
Estimated Expiration
2040-07-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress image distortion and retransfer phenomena in electrophotographic equipment during long-term use, especially the durability problem under different environmental conditions, and miniaturized toner units have a negative impact on image quality.

Method used

By introducing a specific amount of fine particles with controlled volume resistivity into the toner particles, the coverage and distribution of fatty acid metal salts are ensured, and a composite is formed to improve the sliding properties and coating effect of the photosensitive member surface and inhibit nitrogen Oxide adhesion and retransfer.

Benefits of technology

The problems of image shading and retransfer are significantly improved, especially in low temperature and low humidity and high temperature environments, which extend the service life of the equipment and improve the stability of image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002566405360000311
    Figure BDA0002566405360000311
  • Figure BDA0002566405360000341
    Figure BDA0002566405360000341
  • Figure BDA0002566405360000361
    Figure BDA0002566405360000361
Patent Text Reader

Abstract

The present invention relates to a toner. A toner comprising toner particles, the toner particles comprising a binder resin, wherein fine particles A and B are present on the surface of the toner particles; the fine particles A are fatty acid metal salts; the fine particles B have a specific volume resistivity; the average theoretical surface area of ​​the toner particles, the amount of the fine particles A, and the coverage of the toner particle surface by the fine particles A satisfy a specific relationship; the amount of the fine particles B is within a specific range; and the ratio F of the area occupied by a part of the fine particles B embedded in the area near the toner surface in the total area occupied by the fine particles B present in the cross section of one particle of the toner is 50% by area or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner used in an image forming method such as an electrophotographic method. Background Art

[0002] In recent years, there has been a demand for printers with longer life and smaller size, and various properties of toners carried in printers need to be further improved. For example, from the viewpoint of extending the working life, long-term durability needs to be further improved, and from the viewpoint of miniaturization, the volume of each unit needs to be minimized.

[0003] Conventionally, from the viewpoint of improving long-term durability, high-durability photosensitive members such as amorphous silicon photosensitive members and organic photosensitive members having a surface protective layer made of a curable resin have been used to improve the durability of image forming apparatuses. However, it is known that the higher the durability of the photosensitive member, the greater the influence of deterioration of the surface state of the photosensitive member on image quality.

[0004] One of the factors causing the surface change of the photosensitive member that affects the image quality is nitrogen oxides present in the atmosphere. Nitrogen oxides are gases contained in, for example, exhaust gas of motor vehicles, and are exemplified as air pollutants that have recently become a problem.

[0005] It is known that nitrogen oxides dissolve in water to form an aqueous solution of an electrolyte such as nitric acid. Therefore, if an image forming apparatus is allowed to stand overnight without use under a high temperature and high humidity environment where water easily adheres to the surface of a photosensitive member, the nitrogen oxides dissolve in the water attached to the surface of the photosensitive member to form an aqueous electrolyte solution. As a result, in some cases, the surface of the photosensitive member becomes low in resistance, preventing the formation of a clear electrostatic latent image, and image quality deteriorates (hereinafter referred to as image smearing).

[0006] Meanwhile, from the viewpoint of miniaturization, miniaturization of various units has been attempted. For example, miniaturization of a waste toner container for recovering untransferred toner on a photosensitive drum is desired, but retransfer is an obstacle to such miniaturization.

[0007] When a full-color image is formed using an intermediate transfer member in an electrophotographic image forming apparatus, toners of a plurality of colors are transferred to the intermediate transfer member. At this time, a phenomenon may occur in which the toner transferred to the intermediate transfer member on the upstream side moves from the intermediate transfer member to an electrostatic image bearing member such as a photosensitive member at the time of color transfer on the downstream side. This is retransfer.

[0008] This phenomenon is more likely to occur in toner that is charged due to long-term use, and is more likely to occur in a low-temperature and low-humidity environment. Since the retransferred toner is stored in the cleaning device as waste toner, if the amount of retransferred toner is large, the size of the waste toner container cannot be reduced. In addition, the occurrence of retransfer may lead to the occurrence of image quality degradation such as a decrease in image density or occurrence of image density unevenness.

[0009] As described above, in order to extend the life of a printer and reduce its size, it is desired to achieve both suppression of image smear and re-transfer.

[0010] In order to suppress image smear, a technique of preventing nitrogen oxides from adhering to the surface of a photosensitive member and removing the nitrogen oxides with an additive has been proposed. For example, a known means for preventing nitrogen oxides from adhering includes adding a fatty acid metal salt as an external additive so as to cover the electrostatic latent image bearing member with the fatty acid metal salt, thereby suppressing the adhesion of nitrogen oxides.

[0011] Japanese Patent Application Laid-Open No. 2017-116849 proposes a toner in which the adhesion state of a fatty acid metal salt on the toner is controlled.

[0012] Furthermore, Japanese Patent Application Laid-Open No. 2013-164477 proposes to achieve both charging stability and cleaning properties by externally adding silica, titanium oxide, and fatty acid metal salt to toner particles in multiple stages to control the attachment rate of fatty acid metal salt to toner.

[0013] Furthermore, Japanese Patent Application Laid-Open No. 2010-176068 proposes to achieve both optimization of charging and cleaning performance by adding composite fine particles of titanium oxide and silicon dioxide and a fatty acid metal salt.

[0014] Japanese Patent Application Laid-Open No. 2009-003083 proposes improving charging stability by controlling volume resistivity and adding titanium oxide treated with a fatty acid metal salt or the like as an external additive. Summary of the invention

[0015] However, it has been found that, for example, in the toner disclosed in Japanese Patent Application Laid-Open No. 2017-116849, although a certain effect on image smear is confirmed, there is still room for research from the viewpoint of reducing retransfer by also suppressing charging in durable use.

[0016] Therefore, it has been found that there is still room for improvement in the toners in the above-mentioned patent documents with respect to retransfer when used for a long time in a low-temperature and low-humidity environment and image smear when used for a long time in a high-temperature and high-humidity environment.

[0017] The present invention provides a toner that solves the above-mentioned problems. Specifically, the present invention provides a toner that can maintain a clear charge distribution and a member covering effect of a fatty acid metal salt during long-term use, and can also maintain suppression of retransfer and suppression of image smear.

[0018] The present inventors have found that the above-mentioned problems can be solved by causing a fatty acid metal salt necessary for suppressing image smear to be present at a specific coverage ratio in toner particles in which fine particles having a controlled volume resistivity are present near the toner particle surface.

[0019] A toner comprising toner particles, the toner particles comprising a binder resin, wherein

[0020] The fine particles A and the fine particles B are present on the surfaces of the toner particles;

[0021] Fine particles A are fatty acid metal salts;

[0022] The volume resistivity of the fine particles B is 5.0×10Ωm to 1.0×10 8 Ωm;

[0023] when,

[0024] The average theoretical surface area obtained from the number average particle size, particle size distribution and true density of the toner particles measured by a Coulter counter is given by C (m 2 / g) indicates that

[0025] The amount of the fine particles A relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and

[0026] When the coverage of the surface of the toner particle by the fine particles A is represented by E (%),

[0027] Satisfies the following equations (1) and (2):

[0028] 0.03≤D / C≤1.50 (1),

[0029] E / (D / C)≤50.0 (2);

[0030] The amount of the fine particles B is 0.10 parts by mass to 3.00 parts by mass relative to 100 parts by mass of the toner particles; and

[0031] In observation of a cross section of the colorant by a transmission electron microscope, in the total area occupied by fine particles B present in the cross section of one particle of the colorant, a ratio F of an area occupied by a portion of the fine particles B in which the length of a portion of each fine particle B in contact with the colorant particle is more than 50% of the circumference of each fine particle B and which exists in an area near the surface from the outline of the cross section of one particle of the colorant to the inner side of 30 nm toward the center of gravity of the cross section is 50% by area or more.

[0032] The present invention can provide a toner capable of maintaining a clear charge distribution and a member covering effect of a fatty acid metal salt during long-term use, and capable of maintaining suppression of retransfer and suppression of image smear.

[0033] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION

[0034] Unless otherwise specified, the description of a numerical range in the present invention such as "from XX to YY" or "XX to YY" includes the numerical values ​​of the upper and lower limits of the range.

[0035] As described above, in order to suppress image smear, it is important to prevent nitrogen oxides from adhering to the photosensitive member surface, and coating the photosensitive member surface with a fatty acid metal salt is known to be effective in this regard.

[0036] Meanwhile, it was found that, as the rotation speed of the developing roller and the stirring speed of the developer increased due to the high speed of the printer, the conventional toner including the fatty acid metal salt could not maintain the coating effect of the fatty acid metal salt on the surface of the photosensitive member in long-term use under certain processing conditions. The reason is considered to be as follows.

[0037] In conventional toners, external additives such as silica or titanium oxide particles are added in addition to fatty acid metal salts. Fatty acid metal salts are ductile materials that are easily deformed, and spread on the surfaces of toner particles by being sheared. At this time, the fatty acid metal salts capture silica and titanium oxide, that is, external additives such as silica and titanium oxide are easily detached from the toner particle surfaces, so that charging becomes uneven and image defects such as fogging occur.

[0038] Furthermore, it has been found that conventional toners including fatty acid metal salts have a problem in that retransfer is easily caused due to the speeding up of printers. The reason for this is considered to be as follows.

[0039] It is considered that in the case of negatively charged colorant, the colorant transferred (primary transfer) to the intermediate transfer member in the image forming unit on the upstream side is discharged when passing through the potential portion of the non-image portion of the photosensitive member in the image forming unit on the downstream side, and the polarity is reversed from negative to positive, thereby causing re-transfer of the colorant onto the photosensitive member.

[0040] In particular, it is believed that when an image is formed by toners stacked in multiple layers on an intermediate transfer member, the polarity of the toner of the lower layer is more easily reversed, and the toner of the upper layer may be excessively charged (charged up), so retransfer is likely to occur. In particular, in a low temperature and low humidity environment, the polarity reversal of the toner becomes excessive, and retransfer is more likely to occur.

[0041] As described above, assuming that printers will become faster and smaller in size in the future, it is important to suppress image smear in a toner using a fatty acid metal salt to achieve the following two results. Therefore, it is important to (1) improve the effect of maintaining the coating film of the fatty acid metal salt on the surface of the photosensitive member and (2) suppress retransfer caused by the use of the fatty acid metal salt.

[0042] First, let us consider how to maintain the coating effect of the fatty acid metal salt on the surface of the photosensitive member.

[0043] As described above, since the fatty acid metal salt has high ductility, when the friction intensity increases, the metal salt easily spreads and easily captures fine particles such as silicon dioxide and titanium oxide. In addition, the stretched fatty acid metal salt is difficult to move to the surface of the photosensitive member due to the increased adhesion to the surface of the toner particles, and cannot fully cover the surface of the photosensitive member. Therefore, it is important that the fatty acid metal salt particles are attached to the surface of the toner particles in their original form without stretching.

[0044] Next, the inventors have considered a method for suppressing retransfer due to toner charging. It is necessary for the toner to have an optimal charge amount, but it has been considered that a structure that ensures leakage of excess charge to maintain the optimal charge amount and suppress charging in long-term use is important. For this purpose, the use of fine particles with controlled volume resistivity has been considered.

[0045] However, it is found that when fine particles with controlled volume resistivity such as external additives are arranged on the outermost surface of the toner, charge leakage is more likely to occur, and the optimum charge amount is difficult to maintain. Therefore, by arranging a specific amount of fine particles with controlled volume resistivity near the surface of the toner particles, charging can be suppressed while maintaining the optimum charge amount, and re-transfer can be suppressed even after long-term use.

[0046] Furthermore, by disposing fine particles having a controlled volume resistivity near the surface of the toner particles and disposing the fatty acid metal salt in a particle form without depolymerization or stretching on the toner surface, the problems of image smear and retransfer can be solved. It is considered that by such a configuration, when the fatty acid metal salt moves to the surface of the photosensitive member, since some fine particles having a controlled volume resistivity are contained therein, image smear can be greatly improved.

[0047] The present inventors presume that this is because the fatty acid metal salt moves and contains some fine particles having a controlled volume resistivity to form a complex, thereby significantly improving the sliding property on the photosensitive member surface and being able to uniformly coat the photosensitive member surface.

[0048] It has been found that, with this toner, retransfer can be suppressed even in long-term durable use in a low-temperature, low-humidity environment, and image smear can be significantly suppressed in a high-temperature, high-humidity environment. The present invention has been achieved based on this finding.

[0049] Specifically, a toner is provided, comprising toner particles, the toner particles including a binder resin, wherein

[0050] The fine particles A and the fine particles B are present on the surfaces of the toner particles;

[0051] Fine particles A are formed from fatty acid metal salts;

[0052] The volume resistivity of the fine particles B is 5.0×10Ωm to 1.0×10 8 Ωm;

[0053] Wherein the average theoretical surface area obtained from the number average particle size, particle size distribution and true density of the toner particles measured by a Coulter counter is represented by C (m 2 / g), the amount of fine particles A relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and the coverage of the surface of the toner particles by the fine particles A is represented by E (%), satisfying the following formulae (1) and (2);

[0054] The amount of the fine particles B is 0.10 parts by mass to 3.00 parts by mass relative to 100 parts by mass of the toner particles; and

[0055] In observation of a cross section of the toner by a transmission electron microscope, in the total area occupied by the fine particles B present in the cross section of one particle of the toner, a ratio F of an area occupied by a portion of the fine particles B in which the length of a portion of each fine particle B in contact with the toner particle is 50% or more of the circumference of each fine particle B and which is present in a region near the surface from the outline of the cross section of one particle of the toner to the inside of 30 nm toward the center of gravity of the cross section is 50% by area or more:

[0056] 0.03≤D / C≤1.50 (1)

[0057] E / (D / C)≤50.0 (2).

[0058] It is important that the volume resistivity of the fine particles B is 5.0×10Ωm to 1.0×10 8 When the volume resistivity is less than 5.0×10Ωm, it is difficult for the toner to maintain an appropriate charged power, and the image density tends to decrease. When the volume resistivity is greater than 1.0×10Ωm, the toner may have difficulty maintaining an appropriate charged power, and the image density may tend to decrease. 8 When the thickness is less than Ωm, the charge is less likely to leak during charging and re-transfer is more likely to occur.

[0059] The volume resistivity of the fine particles B is preferably 1.0×10 2 Ωm to 5.0×10 7 Ωm, and more preferably 1.0×10 4 Ωm to 5.0×10 7 Ωm.

[0060] Furthermore, composite oxide fine particles using two or more kinds of metals may also be used, and one kind of fine particles or two or more kinds of fine particles selected by arbitrarily combining particles in these fine particle groups may also be used.

[0061] The volume resistivity can be controlled by the calcination temperature and the amount of the surface treatment agent when producing titanium oxide.

[0062] In order to satisfactorily suppress retransfer in long-term use, it is important that the amount of fine particles B in the toner is 0.10 parts by mass to 3.00 parts by mass relative to 100 parts by mass of the toner particles. When the amount is less than 0.10 parts by mass, it is difficult to leak charge when charged, and retransfer is likely to occur, and when the amount exceeds 3.00 parts by mass, it is difficult for the toner to maintain sufficient charging power, and the image density tends to decrease.

[0063] The amount of the fine particles B in the toner is preferably 0.30 parts by mass to 2.50 parts by mass, and more preferably 0.50 parts by mass to 2.50 parts by mass, relative to 100 parts by mass of the toner particles.

[0064] In observation of a cross section of the toner by a transmission electron microscope TEM, in the total area occupied by the fine particles B present in the cross section of one particle of the toner, a ratio F of an area occupied by a portion of the fine particles B in which the length of a portion of each fine particle B in contact with the toner particle is 50% or more of the circumference of each fine particle B and which is present in a surface vicinity region from the outline of the cross section of one particle of the toner to the inside of 30 nm toward the center of gravity of the cross section is 50% or more. Within this range, retransfer and image smear can be suppressed.

[0065] The ratio F in the above range indicates that most of the fine particles B are embedded in the toner particles and exist near the toner particle surface. With this structure, the charge can be leaked and the optimum charge can be maintained even in long-term use, so retransfer can be easily suppressed.

[0066] When F is less than 50 area %, many fine particles B are not embedded in the toner particles. Therefore, in long-term use, the fine particles B are separated from the toner or can be more easily captured when the fatty acid metal salt in the form of the fine particles A moves to the surface of the photosensitive member. As a result, the toner is easily charged and retransfer is likely to occur.

[0067] The ratio F is preferably 60 area % or more, and more preferably 70 area % or more. Meanwhile, the upper limit is not particularly limited, but is preferably 100 area % or less. The ratio F can be controlled by changing the production conditions when the fine particles B are added to the toner particles, the glass transition temperature Tg (° C.) of the toner particles, and the number average particle size of the primary particles of the fine particles B.

[0068] The number average particle size of primary particles of the fine particles B is preferably 5 nm to 50 nm so that the particles can function as leakage points during charging. More preferably, the number average particle size is 5 nm to 25 nm.

[0069] It is preferred that the fine particles C exist on the surface of the toner particles. The fine particles C are preferably silica fine particles. The number average particle diameter of primary particles of the fine particles C is preferably 5 nm to 50 nm, and more preferably 5 nm to 30 nm.

[0070] Silica fine particles with a particle size of 5nm to 50nm are easily electrostatically aggregated and difficult to deagglomerate. However, when the fine particles B are present on the surface of the toner particles, the electrostatic aggregation of the fine silica particles is moderate, and the dispersibility of the fine silica particles on the surface of the toner particles is easily improved. Therefore, by externally adding the external additive C, it is easy to make the charge distribution on the surface of the toner particles uniform, and the charge distribution can be sharpened. As a result, the image density uniformity is improved.

[0071] From the viewpoint of image density uniformity, it is preferred that, in observation of a cross section of the colorant by a transmission electron microscope, of the total area occupied by fine particles C present in the cross section of one particle of the colorant, the ratio of the area occupied by a portion of the fine particles C in which the length of the portion in contact with the colorant particle is more than 50% of the circumference of each fine particle C and which exists in the vicinity of the surface from the contour of the cross section of one particle of the colorant to the inner side of 30 nm toward the center of gravity of the cross section is less than 40 area %.

[0072] The area ratio is preferably 35 area % or less, more preferably 28 area % or less. Meanwhile, the lower limit is not particularly limited, but is preferably 0 area % or more.

[0073] That is, most of the fine particles C show no embedding in the toner particles. As a result, the fine particles B and the fine particles C near the toner particle surface interact with each other, improving the dispersibility of the fine particles C on the toner particle surface and further improving the uniformity of image density.

[0074] The ratio of the area occupied by the fine particles C can be controlled by changing the production conditions when the fine particles C are added to the toner particles, the glass transition temperature Tg (° C.) of the toner particles, and the number average particle size of the primary particles of the fine particles C.

[0075] The amount of the fine particles C is preferably 0.3 parts by mass to 2.0 parts by mass relative to 100 parts by mass of the toner particles.

[0076] Hereinafter, the fine particles A will be described. The fine particles A are formed of a fatty acid metal salt.

[0077] The fatty acid metal salt is preferably a salt of at least one metal selected from the group consisting of zinc, calcium, magnesium, aluminum and lithium. In addition, more preferably fatty acid zinc salt or fatty acid calcium salt, even more preferably fatty acid zinc salt. When these are used, the effect of the present invention is more obvious.

[0078] As the fatty acid of the fatty acid metal salt, a higher fatty acid having 8 to 28 carbon atoms (more preferably, 12 to 22 carbon atoms) is preferred. The metal is preferably a polyvalent metal having a valence of two or more. That is, the fine particles A are preferably a polyvalent metal having a valence of two or more (more preferably divalent or trivalent, more preferably divalent) and a fatty acid metal salt of a fatty acid having 8 to 28 (more preferably 12 to 22) carbon atoms.

[0079] When using a fatty acid having more than 8 carbon atoms, it is easy to suppress the generation of free fatty acids. The amount of free fatty acids is preferably 0.20 mass % or less. In the case where the fatty acid has less than 28 carbon atoms, the melting point of the fatty acid metal salt will not be too high and it is not easy to hinder the fixability. Stearic acid is particularly preferred as the fatty acid. The polyvalent metal with a divalent or higher valence preferably includes zinc.

[0080] Examples of the fatty acid metal salt include metal stearates such as zinc stearate, calcium stearate, aluminum stearate, lithium stearate, and zinc laurate.

[0081] The average theoretical surface area obtained from the number average particle size, particle size distribution and true density of the toner particles measured by a Coulter counter is given by C (m 2 / g) indicates that

[0082] The amount of the fine particles A relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and

[0083] The coverage of the surface of the toner particles by the fine particles A is represented by E (%), satisfying the following formulae (1) and (2):

[0084] 0.03≤D / C≤1.50 (1)

[0085] E / (D / C)≤50.0 (2).

[0086] Average theoretical surface area C(m 2 / g) is preferably 0.60 to 1.50, and more preferably 0.90 to 1.10.

[0087] The coverage ratio E (%) is preferably 0.3 to 40.0, and more preferably 0.5 to 20.0.

[0088] D / C is an expression that allows understanding of how much fine particles A cover toner particles when the toner particles are spherical, and is defined as “theoretical coverage.” E / (D / C) is an expression that indicates the actual degree of coverage relative to “theoretical coverage.”

[0089] D / C needs to be 0.03 to 1.50. In the case where D / C is less than 0.03, the movement of the fine particles A to the surface of the photosensitive member is insufficient, and it becomes difficult to suppress image smear. Meanwhile, in the case where D / C exceeds 1.50, the suppression of charging by the fine particles B becomes insufficient, and retransfer occurs. D / C is preferably 0.05 to 1.50, and more preferably 0.10 to 1.50.

[0090] It is important that E / (D / C) is 50.0 or less. E / (D / C) of 50.0 or less means that the actual coverage is less than the "theoretical coverage". This means that, as described above, the fatty acid metal salt is attached or fixed to the toner particle surface in the form of particles without stretching.

[0091] When E / (D / C) exceeds 50.0, the fatty acid metal salt is stretched and present on the toner particle surface by external addition. In this case, the charge accumulated in the toner after long-term use cannot be effectively released, and re-transfer occurs.

[0092] E / (D / C) is preferably 45.0 or less, more preferably 40.0 or less. Meanwhile, the lower limit is not particularly limited, but is preferably 3.0 or more, and more preferably 10.0 or more.

[0093] The method of fitting the range of the above formula (2) can be exemplified by designing toner particles and optimizing mixing process conditions.

[0094] The amount of the fatty acid metal salt added (amount D) is preferably 0.02 to 1.80 parts by mass, and more preferably 0.10 to 0.50 parts by mass relative to 100 parts by mass of the toner particles. When the amount added is 0.02 parts by mass or more, the effect of addition can be obtained. When the amount is less than 1.80 parts by mass, adhesion to a developing blade or the like is suppressed, and image defects such as developing streaks are unlikely to occur.

[0095] The volume-based median diameter (D50s) of the fatty acid metal salt (fine particles A) is preferably 0.15 μm to 3.00 μm, and more preferably 0.30 μm to 3.00 μm. In the case where the median diameter is 0.15 μm or more, the fatty acid metal salt is sufficiently transferred to the surface of the photosensitive member, and image smear is easily suppressed. In addition, when the particle diameter is 3.00 μm or less, adhesion to a developing blade or the like is suppressed, and image defects such as development streaks are less likely to occur.

[0096] The fatty acid metal salt preferably has a span value B of 1.75 or less as defined by the following formula (4).

[0097] Span value B = (D95s-D5s) / D50s (4)

[0098] D5s: 5% cumulative diameter on a volume basis of the fatty acid metal salt.

[0099] D50s: 50% cumulative diameter on a volume basis of the fatty acid metal salt.

[0100] D95s: 95% cumulative diameter on a volume basis of the fatty acid metal salt.

[0101] The span value B is an index representing the particle size distribution of the fatty acid metal salt. When the span value B is 1.75 or less, the particle size distribution of the fatty acid metal salt present in the toner becomes smaller, so that better charge stability can be obtained. Therefore, the amount of toner charged with the opposite polarity is reduced, and re-transfer can be suppressed. The span value B is more preferably 1.50 or less because a more stable image is obtained. A more preferred value is 1.35 or less. The lower limit is not particularly limited, but is preferably 0.50 or more.

[0102] When the fixing rate of the fine particles A to the toner particles is represented by G (%), the relationship between the area ratios F and G preferably satisfies the following formula (3), and more preferably satisfies the formula (3').

[0103] 2.0 ≤(100-G) / (100-F)≤8.0 (3)

[0104] 3.0≤(100-G) / (100-F)≤6.0 ​​(3')

[0105] In these ranges, image smear can be greatly suppressed, and development streaks can be suppressed. The above ranges can be achieved by highly embedding the fine particles B and attaching and fixing by the fatty acid metal salt at a low coverage relative to the amount thereof.

[0106] In other words, since the fine particles B partially adhere to the fatty acid metal salt moved to the surface of the photosensitive member in a manner satisfying the above formula and then form a complex, as described above, image smear can be significantly suppressed. In addition, as a result of the fine particles A and the fine particles B forming a complex, the fine particles B also reduce the adhesion of the fine particles A to the blade, so that fusion with the blade is reduced and the particles easily pass through the development blade, whereby development streaks can also be suppressed.

[0107] The fixing rate G (%) of the fine particles A to the toner particles is preferably 0.0 to 8.0, more preferably 0.0 to 6.0.

[0108] The fixing ratio G of the fine particles A can be controlled to a preferred range by controlling the particle diameter of the fine particles A and the mechanical impact force (peripheral speed and stirring time) in the external addition step (step of mixing the toner particles with the fine particles A).

[0109] The fine particles B will be described below. The volume resistivity of the fine particles B may be 5.0×10 Ωm to 1.0×10 8 Ωm, and preferably contains at least one particle selected from the group consisting of titanium oxide fine particles, strontium titanate fine particles and aluminum oxide fine particles. More preferably, the fine particles B are at least one particle selected from the group consisting of titanium oxide fine particles, strontium titanate fine particles and aluminum oxide fine particles. More preferably, at least one particle selected from the group consisting of titanium oxide fine particles and strontium titanate fine particles is used, and strontium titanate is even more preferred.

[0110] Since strontium titanate has a hexahedral shape and can increase the contact area with the toner particles, the charge accumulated in the toner particles due to long-term use can be effectively released. In addition, composite oxide fine particles using two or more metals can also be used, and two or more selected from any combination of these fine particle groups can also be used.

[0111] The fine particles B may be surface-treated for the purpose of imparting hydrophobicity.

[0112] Examples of the hydrophobizing agent include chlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, tert-butyldimethylchlorosilane, vinyltrichlorosilane, and the like;

[0113] Alkoxysilanes, for example tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane Silane, isobutyl triethoxysilane, decyl triethoxysilane, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane and γ-(2-aminoethyl)aminopropyl methyl dimethoxysilane, etc.;

[0114] Silazanes, such as hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane, hexaphenyldisilazane, divinyltetramethyldisilazane and dimethyltetravinyldisilazane;

[0115] Silicone oils, such as dimethyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, alkyl-modified silicone oil, chloroalkyl-modified silicone oil, chlorophenyl-modified silicone oil, fatty acid-modified silicone oil, polyether-modified silicone oil, alkoxy-modified silicone oil, carbitol-modified silicone oil, amino-modified silicone oil, fluorine-modified silicone oil and terminal reactive silicone oil;

[0116] Siloxanes, such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane and octamethyltrisiloxane.

[0117] Examples of fatty acids and metal salts thereof include long-chain fatty acids such as undecanoic acid, lauric acid, tridecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, pentadecanoic acid, octadecanoic acid, heptadecanoic acid, eicosanoic acid, octacosanoic acid, oleic acid, linoleic acid and arachidonic acid, and salts of the fatty acids with metals such as zinc, iron, magnesium, aluminum, calcium, sodium and lithium.

[0118] Among these, alkoxysilanes, silazanes and silicone oils are preferably used because they promote hydrophobic treatment. One of these hydrophobizing agents may be used alone, or two or more thereof may be used in combination.

[0119] The fine particles C will be described below. The fine particles C are formed of silica fine particles and may be those obtained by a dry method such as fumed silica, or those obtained by a wet method such as a sol-gel method, etc. From the viewpoint of chargeability, silica fine particles obtained by a dry method are preferably used.

[0120] In addition, the fine particles C may be surface treated for the purpose of imparting hydrophobicity and fluidity. The hydrophobicization method may be exemplified by a method for chemically treating an organosilicon compound that reacts with or physically adsorbs the silica fine particles. In a preferred method, silica generated by gas phase oxidation of a silicon halide is treated with an organosilicon compound. Examples of such organosilicon compounds are listed below.

[0121] Hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, methyltrichlorosilane, allyldimethylchlorosilane, allylphenyldichlorosilane, and benzyldimethylchlorosilane.

[0122] Other examples include bromomethyldimethylchlorosilane, α-chloroethyltrichlorosilane, β-chloroethyltrichlorosilane, chloromethyldimethylchlorosilane, triorganosilylmercaptan, trimethylsilylmercaptan, and triorganosilylacrylate.

[0123] Furthermore, other examples include vinyldimethylacetoxysilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, and 1-hexamethyldisiloxane.

[0124] Other examples include 1,3-divinyltetramethyldisiloxane, 1,3-diphenyltetramethyldisiloxane, and dimethylpolysiloxane having 2 to 12 siloxane units per molecule and one hydroxyl group in the terminal unit for each Si. These are used alone or in combination of two or more.

[0125] In the silica treated with silicone oil, the preferred silicone oil has a 30 mm 2 / s to 1000mm 2 / s viscosity at 25°C.

[0126] Examples include dimethyl silicone oil, methylphenyl silicone oil, α-methylstyrene-modified silicone oil, chlorophenyl silicone oil, and fluorine-modified silicone oil.

[0127] The following methods can be used for silicone oil treatment.

[0128] A method in which silica treated with a silane coupling agent and silicone oil are directly mixed using a mixer such as a Henschel mixer.

[0129] A method of spraying silicone oil onto silica as a base. Alternatively, a method of dissolving or dispersing silicone oil in an appropriate solvent, then adding silica, mixing, and removing the solvent.

[0130] The silica treated with silicone oil is more preferably heated to a temperature of 200° C. or higher (more preferably 250° C. or higher) in an inert gas after being treated with silicone oil to stabilize the surface coating.

[0131] A preferred silane coupling agent is hexamethyldisilazane (HMDS).

[0132] In order to improve the properties of the toner, the toner may further contain other external additives.

[0133] A preferred production method for adding fine particles A, fine particles B, and fine particles C will be described below.

[0134] In order to produce a structure in which fine particles B are embedded in the toner particle surface while preventing fine particles A from being embedded, it is preferred to divide the step of adding fine particles B and fine particles A into two stages. That is, it is preferred to include a step of adding fine particles B to toner particles and a step of adding fine particles A (and optionally fine particles C) to toner particles to which fine particles B have been added.

[0135] In the step of adding fine particles B and fine particles A to the toner particles, the fine particles may be added as external additives by a dry method, may be added by a wet method, or may use each method in two stages. In particular, from the viewpoint of controllability of the presence state of fine particles B and fine particles A, it is preferred to use a two-stage external addition process.

[0136] In order to embed the fine particles B into the surface of the toner particles, it is preferred to heat the external addition apparatus (the step of mixing the fine particles B and the toner particles) in the external addition step, and embed the fine particles B by heating. A mechanical impact force may be applied to embed the fine particles B into the surface of the toner particles slightly softened by heating. In addition, a method of mixing the toner particles and the fine particles B in the external addition step and then performing a heating step in the same apparatus or another apparatus to embed the fine particles B may be used.

[0137] In order to achieve embedding of the fine particles B, it is preferred to set the temperature of the external adding step to around the glass transition temperature Tg of the toner particles.

[0138] Temperature T in the external addition step of fine particles B B Preferably Tg-10℃≤T B ≤Tg+5°C, where Tg is the glass transition temperature of the toner particles.

[0139] Furthermore, the glass transition temperature Tg of the toner particles is preferably 40°C to 70°C, and more preferably 50°C to 65°C, from the viewpoint of storage stability.

[0140] As an apparatus used in the external addition step of the fine particles B, an apparatus having a mixing function and a function of providing a mechanical impact force is preferred, and a known mixing processing apparatus can be used. For example, by using a known mixer such as FM MIXER (manufactured by Nippon Coke Industry Co., Ltd.), SUPER MIXER (manufactured by Kawata Mfg. Co., Ltd.), or HYBRIDIZER (manufactured by Nara Machinery Co., Ltd.), and by heating, the fine particles B can be embedded in the toner particles.

[0141] The dispersion evaluation index of the fine particles B on the toner surface is preferably 0.4 or less, and more preferably 0.3 or less. The lower limit is not particularly limited, but is preferably 0.0 or more. Within the above range, the fine particles B effectively function as charge leakage sites. It is preferred to set external addition conditions so that the dispersibility of the fine particles B is improved.

[0142] The following describes a preferred method of adding fine particles A to toner particles already embedded with fine particles B. It is important that most of the fine particles A are not embedded in the toner particles. To achieve such a structure, the same apparatus used in the step of externally adding fine particles B can be used.

[0143] When the fine particles A are externally added, the mixer does not need to be heated, and the temperature T in the external addition step of the fine particles A is A The glass transition temperature Tg of the toner preferably satisfies the condition T A ≤Tg-15℃.

[0144] Next, a description will be given of a preferred method of adding fine particles C to toner particles embedded with fine particles B. Fine particles C are preferably added in a dry external addition step, and the same apparatus used in the external addition step of fine particles B can be used.

[0145] When the fine particles C are externally added, the mixer does not need to be heated, and the temperature T in the external addition step of the fine particles C is C The glass transition temperature Tg of the toner preferably satisfies the condition T C ≤Tg-15° C. The timing of adding particles C may be such that fine particles A and fine particles C are simultaneously externally added to toner particles in which fine particles B have been embedded, or such that fine particles C are externally added after fine particles A have been added to toner particles in which fine particles B have been embedded.

[0146] The method for producing the toner particles is described. The method for producing the toner particles is not particularly limited, and a known method such as a kneading pulverization method or a wet production method can be used. A wet method is preferably used to obtain a uniform particle size and control the particle shape. Examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization coagulation method, and an emulsion coagulation method, and the emulsion coagulation method can be preferably used.

[0147] In the emulsion aggregation method, fine particles of a binder resin and other materials such as a colorant as needed are dispersed and mixed in an aqueous medium containing a dispersion stabilizer. A surfactant may also be added to the aqueous medium. A coagulant is then added to aggregate the mixture until the desired toner particle size is reached, and the fine resin particles are also melted and attached together after or during aggregation. Shape control by heating may also be performed in this method as needed to form toner particles.

[0148] The fine particles of the binder resin here may be composite particles formed as multilayer particles including two or more layers composed of different resins, for example, which may be produced by emulsion polymerization, microemulsion polymerization, phase inversion emulsification, etc., or by a combination of a plurality of production methods.

[0149] When the toner particles contain an internal additive, the internal additive may be contained in the resin fine particles. It is also possible to separately prepare a dispersion of internal additive fine particles consisting only of the internal additive, and then the internal additive fine particles may be aggregated with the resin fine particles at the time of aggregation. Resin fine particles of different compositions may also be added at different times during aggregation, and aggregated to prepare toner particles consisting of layers of different compositions.

[0150] The following can be used as dispersion stabilizers:

[0151] Inorganic dispersion stabilizers include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silicon dioxide, and aluminum oxide.

[0152] Other examples include organic-based dispersion stabilizers such as polyvinyl alcohol, gelatin, methyl cellulose, methyl hydroxypropyl cellulose, ethyl cellulose, carboxymethyl cellulose sodium salt, and starch.

[0153] A known cationic surfactant, anionic surfactant or nonionic surfactant can also be used as the surfactant.

[0154] Specific examples of the cationic surfactant include dodecylammonium bromide, dodecyltrimethylammonium bromide, dodecylpyridinium chloride, dodecylpyridinium bromide, hexadecyltrimethylammonium bromide and the like.

[0155] Specific examples of the nonionic surfactant include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, sorbitan monooleate polyoxyethylene ether, styrylphenyl polyoxyethylene ether, monodecanoyl sucrose, and the like.

[0156] Specific examples of the anionic surfactant include fatty soaps such as sodium stearate and sodium laurate, and sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene (2) lauryl ether sulfate, and the like.

[0157] Next, the binder resin constituting the toner will be described.

[0158] Preferred examples of the binder resin include vinyl resins, polyester resins, and the like. Examples of vinyl resins, polyester resins, and other binder resins include the following resins and polymers:

[0159] Monomers of styrene and substituted styrenes, such as polystyrene and polyvinyltoluene; styrene copolymers, such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers and styrene maleate copolymers; and polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resins, polyamide resins, epoxy resins, polyacrylic resins, rosin, modified rosin, terpene resins, phenol resins, aliphatic or alicyclic hydrocarbon resins and aromatic petroleum resins.

[0160] These binder resins may be used alone or in combination.

[0161] Examples of polymerizable monomers that can be used to produce vinyl resins include styrene monomers such as styrene and α-methylstyrene; acrylates such as methyl acrylate and butyl acrylate; methacrylates such as methyl methacrylate, 2-hydroxyethyl acrylate, tert-butyl methacrylate and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic acid anhydrides such as maleic anhydride; nitrile vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitrovinyl monomers such as nitrostyrene.

[0162] The binder resin preferably contains a carboxyl group, and preferably a resin made of a polymerizable monomer containing a carboxyl group. The polymerizable monomer containing a carboxyl group includes, for example, vinyl carboxylic acids, such as acrylic acid, methacrylic acid, α-ethyl acrylic acid and crotonic acid; unsaturated dicarboxylic acids, such as fumaric acid, maleic acid, citraconic acid and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives, such as monoacryloxyethyl succinate, monomethacryloxyethyl succinate, monoacryloxyethyl phthalate and monomethacryloxyethyl phthalate.

[0163] The polycondensate of the carboxylic acid component and the alcohol component listed below can be used as the polyester resin. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid and trimellitic acid. Examples of the alcohol component include bisphenol A, hydrogenated bisphenol, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, glycerol, trimethylolpropane and pentaerythritol.

[0164] These polyester resins may also be polyester resins containing urea groups. Preferably, the terminal and other carboxyl groups of the polyester resin are not capped.

[0165] In order to control the molecular weight of the binder resin constituting the toner particles, a crosslinking agent may also be added during the polymerization of the polymerizable monomer.

[0166] Examples include ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, diacrylates of polyethylene glycol #200, #400 and #600, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester diacrylate (MANDA, Nippon Kayaku Co., Ltd.), and those in which acrylate is replaced with methacrylate.

[0167] The amount of the crosslinking agent added is preferably 0.001 parts by mass to 15.000 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0168] The toner particles preferably contain a release agent. Preferably, the toner particles contain an ester wax having a melting point of 60° C. to 90° C. (more preferably 60° C. to 80° C.). Such a wax is excellent in compatibility with the binder resin, so that a plasticizing effect can be easily obtained, and the fine particles B can be effectively embedded in the toner particle surface.

[0169] Examples of the ester wax include waxes mainly composed of fatty acid esters such as carnauba wax and montanic acid ester wax; fatty acid esters in which the acid component has been partially or completely deacidified, such as deacidified carnauba wax; hydroxyl-containing methyl ester compounds obtained by hydrogenation of vegetable oils and fats, etc.; saturated fatty acid monoesters such as stearyl stearate and behenyl behenate; diesterification products of saturated aliphatic dicarboxylic acids and saturated fatty alcohols such as dibehenyl sebacate, distearyl dodecanedioate and distearyl octadecanediol; diesterification products of saturated aliphatic diols and saturated aliphatic monocarboxylic acids such as nonanediol dibehenate and dodecanediol distearate.

[0170] Among these waxes, it is desirable to include difunctional ester waxes (diester) having two ester bonds in the molecular structure.

[0171] The difunctional ester wax is an ester compound of a dihydric alcohol and an aliphatic monocarboxylic acid, or an ester compound of a divalent carboxylic acid and an aliphatic monohydric alcohol.

[0172] Specific examples of the aliphatic monocarboxylic acid include tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, behenic acid, tetracosanoic acid, hexacosanoic acid, octacosanoic acid, triacontanoic acid, oleic acid, vaccenic acid, linoleic acid, and linolenic acid.

[0173] Specific examples of the fatty monohydric alcohols include myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, and triacontanol.

[0174] Specific examples of divalent carboxylic acids include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid, phthalic acid, isophthalic acid, terephthalic acid, and the like.

[0175] Specific examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosandiol, 1,30-triacontandiol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiro glycol, 1,4-phenylene glycol, bisphenol A, hydrogenated bisphenol A, and the like.

[0176] Other release agents that can be used include petroleum waxes and their derivatives, such as paraffin wax, microcrystalline wax and vaseline, montan wax and its derivatives, hydrocarbon waxes obtained by the Fischer-Tropsch process and their derivatives, polyolefin waxes and their derivatives such as polyethylene and polypropylene, natural waxes and their derivatives such as carnauba wax and candelilla wax, higher fatty alcohols and fatty acids such as stearic acid and palmitic acid.

[0177] The content of the release agent is preferably 5.0 parts by mass to 20.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0178] A colorant may also be contained in the toner. The colorant is not particularly limited, and the following known colorants may be used.

[0179] Examples of yellow pigments include yellow iron oxide, Naples yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, condensed azo compounds such as tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include:

[0180] CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168 and 180.

[0181] Examples of red pigments include red iron oxide, permanent red 4R, lithol red, pyrazolone red, viewing red calcium salt, lake red C, lake red D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, condensed azo compounds such as alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include:

[0182] CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221 and 254.

[0183] Examples of blue pigments include alkali blue lakes, Victoria blue lakes, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue metachloride, fast sky blue, copper phthalocyanine compounds such as Indanthrene Blue BG and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include:

[0184] CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62 and 66.

[0185] Examples of black pigments include carbon black and aniline black. These colorants may be used alone, as a mixture, or in a solid solution.

[0186] The content of the colorant is preferably 3.0 parts by mass to 15.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0187] The toner particles may also contain a charge control agent. Known charge control agents may be used. A charge control agent that provides a fast charging speed and can stably maintain a uniform charge amount is particularly desirable.

[0188] Examples of the charge control agent for controlling the negative chargeability of toner particles include:

[0189] Organometallic compounds and chelate compounds, including monoazo metal compounds, acetylacetonate metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, and metal compounds of oxycarboxylic acids and dicarboxylic acids. Other examples include aromatic oxycarboxylic acids, aromatic monocarboxylic acids and polycarboxylic acids and their metal salts, anhydrides and esters, and phenol derivatives such as bisphenol, etc. Other examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarene.

[0190] On the other hand, examples of charge control agents for controlling the positive charge of colorant particles include aniline black and aniline black modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts, such as tributylbenzylammonium-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, onium salts, such as phosphonium salts of these analogs and lake pigments of these; triphenylmethane dyes and lake pigments thereof (using phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide or ferrocyanide, etc. as lake agents); metal salts of higher fatty acids; and resin charge control agents.

[0191] These charge control agents may be used alone or in combination of two or more thereof. The amount of these charge control agents added is preferably 0.01 to 10.00 parts by mass based on 100.00 parts by mass of the polymerizable monomer.

[0192] The methods used to measure various physical properties are described below.

[0193] Determination of median diameter and span value of fine particles A

[0194] The volume-based median diameter of the fatty acid metal salt is measured in accordance with JIS Z 8825-1 (2001), and is specifically as follows.

[0195] A laser diffraction / scattering type particle size distribution measuring device "LA-920" (manufactured by Horiba, Ltd.) was used as a measuring device. The measuring conditions were set, and the dedicated software "HORIBA LA-920for The measurement data were analyzed using "WET (LA-920) Ver. 2.02". In addition, ion-exchanged water from which impurities and solids had been removed in advance was used as a measurement solvent.

[0196] The assay steps are as follows.

[0197] (1) Install the batch-type holder on the LA-920.

[0198] (2) A predetermined amount of ion exchange water is put into a batch cell, and the batch cell is set in a batch cell holder.

[0199] (3) Use a dedicated stirrer head to stir the interior of the batch tank.

[0200] (4) Press the "Refractive Index" button on the "Display Condition Setting" interface and select the file "110A000I" (relative refractive index 1.10).

[0201] (5) On the "Display Condition Settings" screen, the particle size is set based on volume.

[0202] (6) After a warm-up period of more than 1 hour, perform optical axis adjustment, optical axis fine-tuning, and blank measurement.

[0203] (7) About 60 ml of ion exchange water was placed in a 100 ml glass flat-bottom beaker. As a dispersant, about 0.3 ml of "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments; pH 7 and containing a nonionic surfactant, anionic surfactant and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted by about three times the mass of ion exchange water was added.

[0204] (8) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Inc.) having an electrical output of 120 W and in which two oscillators having an oscillation frequency of 50 kHz and a phase shift of 180 degrees were built was prepared. About 3.3 L of ion-exchanged water was put into the water tank of the ultrasonic disperser, and 2 ml of CONTAMINON N was added to the water tank.

[0205] (9) The beaker of (7) is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous solution in the beaker is maximized.

[0206] (10) While the aqueous solution in the beaker of (9) is irradiated with ultrasonic waves, about 1 mg of a fatty acid metal salt is added little by little to the aqueous solution in the beaker and dispersed. Then, the ultrasonic dispersion treatment is continued for an additional 60 seconds. In this case, the fatty acid metal salt sometimes floats on the liquid surface in the form of a block. In this case, the block is immersed in water by shaking the beaker, and then ultrasonic dispersion is performed for 60 seconds. Under ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.

[0207] (11) The aqueous solution prepared in (10) in which the fatty acid metal salt has been dispersed is immediately added little by little to the batch cell while being careful not to introduce air bubbles, and the transmittance of the tungsten lamp is adjusted to 90% to 95%. Then, the particle size distribution is measured. Based on the obtained volume-based particle size distribution data, the 5% cumulative diameter, 50% cumulative diameter, and 95% cumulative diameter on the small particle size side are calculated.

[0208] The obtained values ​​are represented by D5s, D50s, and D95s, and the span value is determined from these values.

[0209] Method for measuring true density of toner particles

[0210] When the true density of toner particles in a toner in which an external additive is externally added to the toner particles is measured, the external additive is removed. A specific method is described below.

[0211] A total of 160 g of sucrose (manufactured by Kishida Chemical) was added to 100 mL of ion exchange water and dissolved in a water bath to prepare a concentrated sucrose solution. A total of 31 g of concentrated sucrose solution and 6 ml of CONTAMINON N were placed in a centrifuge tube to prepare a dispersion. A total of 1 g of toner was added to the dispersion, and the blocks of the toner were loosened with a scraper or the like.

[0212] The centrifuge tube was vibrated on a shaker ("KM Shaker", manufactured by Iwaki Sangyo Co., Ltd.) for 20 min at 350 vibrations per minute. After the vibration, the solution was transferred to a glass tube (50 mL) for a horizontal rotor and centrifuged in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 min. In the glass tube after the centrifugation, the toner particles were present in the uppermost layer, and the external additive was present in the lower layer on the aqueous solution side, so that only the toner particles in the uppermost layer were collected.

[0213] If the external additive is not sufficiently removed, centrifugation is repeated as necessary, and after sufficient separation, the toner liquid is dried to collect toner particles.

[0214] The true density of the toner particles is measured by a dry type automatic densitometer-automatic pycnometer (manufactured by Yuasa Ionics Co., Ltd.) The conditions are as follows.

[0215] Pool: SM pool (10ml)

[0216] Sample volume: about 2.0g

[0217] This method measures the true density of solids and liquids based on the gas phase displacement method. Similar to the gas phase displacement method, it is based on the Archimedean principle, but because gas (argon) is used as the displacement medium, the micropore accuracy is high.

[0218] Method for measuring weight average particle size (D4) and number average particle size (D1) of toner particles

[0219] The weight average particle size (D4) and number average particle size (D1) of the toner particles are calculated as follows. The measurement and analysis are performed using a "Multisizer (R) 3 Coulter Counter" precision particle size distribution analyzer (Beckman Coulter, Inc.) based on the pore resistance method and equipped with a 100 μm pore tube, together with the attached "Beckman Coulter Multisizer3 Version 3.51" software (Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data.

[0220] The electrolytic aqueous solution used in the measurement may be a solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1 mass %, for example, "ISOTON II" (Beckman Coulter, Inc.).

[0221] The following settings were performed using dedicated software prior to measurement and analysis.

[0222] On the "Change Standard Measurement Method (SOM)" screen of the dedicated software, the total count number in the control mode was set to 50,000 particles, the number of measurements was set to 1, and the Kd value was set to the value obtained using "Standard Particles 10.0 μm" (Beckman Coulter, Inc.). The threshold noise level was automatically set by pressing the "Threshold / Noise Level Determination" button. The current was set to 1600 μA, the gain was set to 2, the electrolyte was set to ISOTON II, and the "Rinse the orifice tube after measurement" checkbox was entered.

[0223] On the "Conversion Settings from Pulse to Particle Size" interface of the dedicated software, the element interval was set to logarithmic particle size, the particle size element was set to 256, and the particle size range was set to 2 μm to 60 μm.

[0224] The specific measurement method is as follows.

[0225] (1) Add about 200 ml of the electrolytic aqueous solution to a 250 ml glass round-bottom beaker dedicated to the Multisizer3, place the beaker on the sample stand, and stir it counterclockwise at a rate of 24 rps using a stirring rod. Then use the "well flushing" function of the dedicated software to remove contamination and bubbles in the well tube.

[0226] (2) 30 ml of the same electrolytic aqueous solution was placed in a 100 ml flat-bottomed beaker made of glass, and about 0.3 ml of a diluted solution of "Contaminon N" (a 10 mass % aqueous solution of a pH 7 neutral detergent for cleaning precision equipment, containing a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by WakoPure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water was added.

[0227] (3) A prescribed amount of ion-exchanged water was added to the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetra 150" (Nikkaki Bios Co., Ltd.) having an electrical output of 120 W and equipped with two built-in oscillators having an oscillation frequency of 50 kHz and a phase shift of 180° from each other, and about 2 ml of CONTAMINON N was added to the water tank.

[0228] (4) The beaker of (2) is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. The height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolytic aqueous solution in the beaker is maximized.

[0229] (5) The electrolytic aqueous solution in the beaker of (4) above is exposed to ultrasonic waves, while about 10 mg of toner particles are added little by little to the electrolytic aqueous solution and dispersed. Then, ultrasonic dispersion is continued for an additional 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.

[0230] (6) The electrolytic aqueous solution in which the toner particles of (5) are dispersed is dropped into the round bottom beaker of (1) set on the sample stand using a pipette, and the measurement concentration is adjusted to about 5%. Then, the measurement is performed until the number of particles measured reaches 50,000.

[0231] (7) The measurement data is analyzed using the dedicated software included in the equipment, and the weight average particle size (D4) and the number average particle size (D1) are calculated. The number average particle size (D1) and the weight average particle size (D4) are the "arithmetic diameters" on the "Analysis / Number Statistics (Arithmetic Mean)" interface or the "Analysis / Volume Statistics (Arithmetic Mean)" interface when setting the chart / number % or the chart / volume % in the dedicated software.

[0232] Calculation method of average theoretical surface area C per unit mass of toner particles

[0233] After obtaining the number average particle size (D1), the data were analyzed using the dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (provided by Beckman Coulter, Inc.) divides the range of 2.0 to 32.0 μm into 12 channels (2.000 to 2.520 μm, 2.520 to 3.175 μm, 3.175 to 4.000 μm, 4.000 to 5.040 μm, 5.040 to 6.350 μm, 6.350 to 8.000 μm, 8.000 to 10.079 μm, 10.079 to 12.699 μm, 12.699 to 16.000 μm, 16.000 to 20.159 μm, 20.159 to 25.398 μm and 25.398 to 32.000 μm), and determines the number ratio of colorant particles in each particle size range.

[0234] Thereafter, using the median value of each channel (e.g., when the channel is 2.000 to 2.520 μm, the median value is 2.260 μm), a theoretical surface area (=4×π×(median value of each channel)) is obtained assuming that the toner particle of the median value of each channel is a true sphere. 2 ). The theoretical surface area is multiplied by the previously determined ratio of the number of particles belonging to each channel to determine the average theoretical surface area (a) of a toner particle assuming that the toner particle being measured is a true sphere.

[0235] Next, the theoretical mass (=4 / 3×π×(median value of each channel)) is obtained in the same manner from the median value of each channel and the measured true density of the toner particle, assuming that the toner particle having the median value of each channel is a true sphere. 3 × true density). The average theoretical mass (b) of one toner particle is determined from the theoretical mass and the ratio of the number of particles belonging to each channel determined above.

[0236] From the above, it can be seen that the average theoretical surface area C (m 2 / g) is calculated from the average theoretical surface area and the average theoretical mass of one toner particle.

[0237] Method for determining coverage of fine particles A

[0238] The coverage of the fine particles A is measured by ESCA (X-ray Photoelectron Spectroscopy) (Quantum 2000, manufactured by ULVAC-PHI).

[0239] A 75 mm square pressing plate (with a screw hole of about 1 mm in diameter for fixing the sample) mounted on the device was used as a sample holder. Since the screw hole of the pressing plate is a through hole, the hole is sealed with a resin or the like, and a concave portion for measuring a powder with a depth of about 0.5 mm is prepared. The measuring sample (toner or fine particle A (fatty acid metal salt) only) is filled into the concave portion with a scraper or the like, and the sample is prepared by grinding.

[0240] The ESCA measurement conditions are as follows.

[0241] Analytical method: Narrow analysis

[0242] X-ray source: Al-Kα

[0243] X-ray conditions: 100μ, 25W, 15kV

[0244] Photoelectron absorption angle: 45°

[0245] Pass Energy: 58.70eV

[0246] Measuring range: φ100μm

[0247] First, the toner is measured. In order to calculate the quantitative value of the metal atoms contained in the fine particles A, the C1s (BE 280 eV to 295 eV), O 1s (BE 525 eV to 540 eV), Si 2p (BE 95 eV to 113 eV) and element peaks of the metal atoms of the fine particles A are used. The quantitative value of the metal element obtained here is represented by X1.

[0248] Next, elemental analysis of the fine particles A alone is performed in the same manner, and the quantitative values ​​of the elements contained in the fine particles A obtained here are represented by X2.

[0249] The coverage is obtained from the following formula by using X1 and X2.

[0250] Coverage of fine particles A (%) = X1 / X2×100

[0251] Determination of the content of fine particles A and B in toner

[0252] The fine particles A and B are separated from the components of the toner and their amounts are measured by the following method.

[0253] A total of 1 g of the toner was added to a vial containing 31 g of chloroform and dispersed. Dispersion was performed using an ultrasonic homogenizer for 30 min to prepare a dispersion liquid. The treatment conditions were as follows.

[0254] Ultrasonic treatment apparatus: Ultrasonic homogenizer VP-050 (manufactured by Taitec Corporation).

[0255] Microchip: Step-type microchip, tip diameter φ2mm.

[0256] Position of the tip of the microchip: The center of the glass vial is 5 mm high from the bottom of the vial.

[0257] Ultrasonic conditions: 30% intensity, 30 min. At this time, the vial was cooled with ice water while applying ultrasonic waves so as not to increase the temperature of the dispersion.

[0258] The dispersion was transferred to a glass tube (50 mL) for a horizontal rotor and centrifuged at 58.33S / min using a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.). -1 Centrifuge for 30 min. After centrifugation, separate the materials constituting the toner in a glass tube. Extract and dry the materials under vacuum (40° C. / 24 h). Select and extract the fine particles A and B that meet the requirements of the present invention, and measure their contents.

[0259] Method for determining volume resistivity of fine particles B

[0260] The volume resistivity of the fine particles B was calculated from the current value measured using an electrometer (6430 type sub-femtoamp remote source meter, manufactured by Keithley Instruments Co.). A total of 1.0 g of fine particles B were filled in a sample holder of an upper and lower electrode sandwich type (SH2-Z type, manufactured by TOYO Corporation), and the fine particles B were compressed by applying a torque of 2.0 N·m. The electrodes used had an upper electrode diameter of 25 mm and a lower electrode diameter of 2.5 mm. A voltage of 10.0 V was applied to the fine particles B through the sample holder, and the resistance value was calculated from the current value at saturation excluding the charged current, and the volume resistivity was calculated by the following formula.

[0261] The fine particles B can be separated from the toner by dispersing the toner in a solvent such as chloroform and then separating the fine particles B by a specific gravity difference by centrifugation, etc. In the case where the fine particles B can be obtained alone, the fine particles B can also be measured alone.

[0262] Volume resistivity (Ωm) = resistance value (Ω) Electrode area (m 2 ) / sample thickness (m)

[0263] Method for measuring the number average particle size of primary particles of fine particles B

[0264] The number average particle diameter of the primary particles of the fine particles B is measured using a scanning electron microscope "S-4800" (trade name; manufactured by Hitachi, Ltd.). The toner to which the fine particles B have been added is observed, and the major diameters of 100 primary particles of the fine particles B are randomly measured in a field of view magnified to 50,000 times to obtain the number average particle diameter. The observation magnification is appropriately adjusted according to the size of the fine particles B.

[0265] When the fine particles B can be obtained separately, the fine particles B alone can be measured.

[0266] Method for determining the number average particle size of primary particles of fine particles C

[0267] The number average particle diameter of fine particles C is determined in the same manner as the method for determining the number average particle diameter of primary particles of fine particles B. In order to distinguish fine particles A from fine particles B, each particle of the external additive is subjected to EDS analysis, and whether the analyzed particle is fine particle C is determined.

[0268] Method for determining the ratio of the area occupied by embedded fine particles B

[0269] The ratio of the area occupied by the embedded fine particles B was measured using a transmission electron microscope (TEM) (JEM-2100, manufactured by JEOL Ltd.).

[0270] In preparing the sample, the toner to be observed is sufficiently dispersed in the epoxy resin curable at room temperature. Thereafter, the cured product itself obtained by curing in the atmosphere at a temperature of 35°C for 2 days, or a sheet-like sample after freezing obtained by using a microtome equipped with a diamond blade is observed.

[0271] The circle equivalent diameter of the toner is determined from the cross-sectional area in the transmission microscopic image, and the toner in which the value obtained is ±10% of the number average particle diameter of the toner particles determined by the above-mentioned method using the Coulter counter is selected for TEM observation. The following toner cross-sectional image analysis is performed on 100 cross sections.

[0272] For image analysis, image processing software "Image-Pro Plus 5.1J" (manufactured by MediaCybernetics) was used.

[0273] The following will describe the distinction between the embedded fine particles B and the non-embedded fine particles B. In the case where only a portion of the fine particles B is embedded in the toner particles, when the length of the portion where the fine particles B are in contact with the toner particles is 50% or more of the circumference of the fine particles B, the fine particles B are presumed to be embedded. When the length of the portion where the fine particles B are in contact with the toner particles is less than 50%, the fine particles B are presumed to be non-embedded.

[0274] The area used for the colorant cross-sectional image analysis will be described in detail below. The outline of the cross section of the colorant is the outermost surface of the colorant. The portion where the fine particle A or B is the outermost surface and the portion where the colorant particle is the outermost surface are both contained in one particle of the colorant. The area from the outline of the cross section of the colorant to the inner side of 30nm toward the center of gravity of the cross section is defined as the surface vicinity area. When a part or all of the fine particle B embedded in the toner particle is contained inside the toner relative to the surface vicinity area, the area of ​​the part is not included in the area of ​​the embedded fine particle B.

[0275] The ratio F of the area occupied by a portion of the fine particles B embedded in the surface vicinity region is calculated based on the total area occupied by the fine particles B present in the cross section of one particle of the toner.

[0276] A total of 100 cross sections were observed and their arithmetic mean was used.

[0277] Method for determining the ratio of the area occupied by embedded fine particles C

[0278] The ratio of the area occupied by the embedded fine particles C is calculated in the same manner as the method of determining the ratio of the area occupied by the embedded fine particles B.

[0279] In order to distinguish between the fine particles A and the fine particles B, each particle of the external additive is subjected to EDS analysis, and it is determined whether the analyzed particle is the fine particle C.

[0280] Determination of the adhesion ratio G of fine particles A to toner particles

[0281] A total of 160g of sucrose (manufactured by Kishida Chemical) was added to 100mL of ion exchange water and dissolved in a water bath to prepare a concentrated sucrose solution. A total of 31g of concentrated sucrose solution and 6mL of CONTAMINON N (a 10% aqueous solution of a neutral detergent for cleaning precision measurement equipment; pH 7 and containing nonionic surfactants, anionic surfactants and organic detergents, manufactured by Wako Pure Chemical Industries, Ltd.) were placed in a centrifuge tube (capacity 50mL) to prepare a dispersion. A total of 1.0g of toner was added to the dispersion, and the blocks of the toner were loosened with a scraper or the like.

[0282] The centrifuge tube was vibrated on a shaker ("KMShaker", manufactured by IwakiSangyo Co., Ltd.) at 350 spm (vibration per minute) for 20 min. After the vibration, the solution was transferred to a glass tube (capacity 50 mL) in a horizontal rotor and separated in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 min.

[0283] It is visually confirmed that the toner and the aqueous solution are fully separated, and the separated toner in the uppermost layer is collected with a scraper or the like. The aqueous solution containing the collected toner is filtered through a vacuum filter and then dried using a dryer for more than 1 hour. The dried product is depolymerized with a scraper, and the amount of the metal element contained in the fine particles A is determined by X-ray fluorescence. The fixing rate (%) is calculated from the ratio of the element amount of the toner treated with the dispersion to the initial toner to be measured.

[0284] The fluorescent X-ray measurement of each element conforms to JIS K 0119-1969, and the details are as follows.

[0285] A wavelength dispersive X-ray fluorescence spectrometer "Axios" (manufactured by PANalytical) and dedicated software "SuperQ ver.4.0F" (manufactured by PANalytical) for setting measurement conditions and analyzing measurement data were used as the measurement apparatus. Rh was used as the anode of the X-ray tube, the measurement atmosphere was vacuum, the measurement diameter (collimator mask diameter) was 10 mm, and the measurement time was 10 sec. When measuring light elements, a proportional counter (PC) was used, and when measuring heavy elements, a scintillation counter (SC) was used.

[0286] Pellets prepared by placing about 1 g of the dispersion-treated toner or initial toner in a dedicated pressed aluminum ring having a diameter of 10 mm, flattening, and forming into a thickness of about 2 mm by a tablet press "BRE-32" (Maekawa Testing Machine MFG Co., Ltd.) at 20 MPa for 60 seconds were used as measurement samples.

[0287] The measurement was carried out under the above conditions, the element was identified based on the obtained X-ray peak position, and its concentration was calculated from the count rate (unit: cps) of the number of X-ray photons per unit time.

[0288] The quantitative method of the toner will be described, for example, taking the case where the fine particles A are zinc stearate as an example. Fine powder of zinc stearate is added to 100 parts by mass of the toner particles to obtain 0.5 parts by mass, and is fully mixed using a coffee grinder. Similarly, zinc stearate is mixed with the toner particles to obtain 1.0 parts by mass and 2.0 parts by mass, and these mixtures are used as samples for the calibration curve.

[0289] For each sample, pellets for calibration curve samples were prepared using a tablet press as described above, and the net intensity of Kα rays of the metal element of the fatty acid metal salt was measured. The obtained X-ray count rate was plotted on the ordinate, and the amount of fatty acid metal salt added in each calibration curve sample was plotted on the abscissa, thereby obtaining a calibration curve in the form of a linear function.

[0290] Next, using the pellets of the toner to be analyzed, the net intensity of Kα rays of the metal element of the fatty acid metal salt is measured. Then, the amount of the fatty acid metal salt in the toner is determined from the calibration curve. The ratio of the amount of the element in the toner treated with the dispersion calculated by the above method to the amount of the element in the initial toner is determined and regarded as the fixing rate G (%).

[0291] Determination method of dispersion evaluation index of fine particles B

[0292] The calculation of the dispersion evaluation index of the fine particles B in the toner surface was performed using a scanning electron microscope "S-4800". The toner to which the fine particles B were externally added was observed in a field magnified 10,000 times at an accelerating voltage of 1.0 kV in the same field. Using image processing software "Image-Pro Plus 5.1J" (manufactured by Media Cybernetics, Inc.), calculation was performed from the observed image in the following manner.

[0293] Binarization is performed to extract only fine particles B, the number n of fine particles B and the centroid coordinates of all fine particles B are calculated, and the distance dn min between each fine particle B and the nearest fine particle B is calculated. Assuming that the average value of the closest distance between fine particles B in the image is d ave, the dispersion is expressed by the following equation.

[0294]

[0295] The dispersion is determined by random observation of 50 toners through the above procedure, and the average value is used as the dispersion evaluation index. The smaller the dispersion evaluation index, the better the dispersibility.

[0296] Method for determining the melting point of wax and the glass transition temperature Tg of toner particles

[0297] The melting point of the wax and the glass transition temperature Tg of the toner particles were measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The temperature calibration of the device detection unit used the melting points of indium and zinc, and the heat calibration used the melting heat of indium.

[0298] Specifically, about 3 mg of the sample (wax, toner particles) was accurately weighed and placed in an aluminum pan, and an empty aluminum pan was used as a control. The measurement was performed at a temperature increase rate of 10°C / min in the measurement temperature range of 30°C to 200°C. In the measurement, once the temperature was increased to 200°C at a rate of 10°C / min, it was decreased to 30°C at a rate of 10°C / min, and then increased at a rate of 10°C / min.

[0299] The physical properties were determined using the DSC curve obtained in the second temperature increase process. In this DSC curve, the temperature showing the highest endothermic peak of the DSC curve in the temperature range of 30°C to 200°C was defined as the melting point of the sample. In the DSC curve, the intersection between the line of the midpoint of the baseline before and after the specific heat change and the DSC curve was defined as the glass transition temperature Tg.

[0300] Determination of average circularity of toner particles

[0301] The average circularity of the toner particles is measured using a "FPIA-3000" flow particle image analyzer (Sysmex Corporation) under the conditions of measurement and analysis of the calibration operation.

[0302] The specific measurement method is as follows.

[0303] First, about 20 mL of ion exchange water from which solid impurities etc. have been removed is placed in a glass container. Then, about 0.2 mL of a diluted solution of "Contaminon N" (a 10% by mass aqueous solution of a pH 7 neutral detergent for cleaning precision equipment, which contains a nonionic surfactant, anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water is added.

[0304] Then, about 0.02 g of the measurement sample is added and dispersed with an ultrasonic disperser for 2 minutes to obtain a dispersion liquid for measurement. Cooling is appropriately performed during this process so that the dispersion temperature is 10°C to 40°C.

[0305] Using a tabletop ultrasonic cleaner and a disperser having an oscillation frequency of 50 kHz and an electrical output of 150 W (eg, "VS-150" manufactured by Velvo-Clear), a certain amount of ion exchange water is placed in a disperser tank, and about 2 mL of Contaminon N is added to the tank.

[0306] The measurement was performed using a flow particle image analyzer equipped with a "LUCPLFLN" objective lens (magnification 20x, aperture 0.40) and a particle sheath "PSE-900A" (Sysmex Corporation) as a sheath liquid. The dispersion obtained by the above steps was introduced into the flow particle image analyzer, and 2000 toner particles were measured in the total count mode in the HPF measurement mode.

[0307] Then, during particle analysis, the average circularity of the toner particles is determined with a binarization threshold of 85%, and the analyzed particle diameter is limited to a circle-equivalent diameter of at least 1.977 μm to less than 39.54 μm.

[0308] Before starting the measurement, automatic focus adjustment is performed using standard latex particles (for example, Duke Scientific Corporation "RESEARCH AND TEST PARTICLES Latex Microsphere Suspensions 5100A" diluted with ion-exchanged water). After starting the measurement, automatic focus adjustment is performed again every two hours.

[0309] Example

[0310] The present invention is described in more detail below based on Examples and Comparative Examples, but the present invention is by no means limited thereto. Unless otherwise specified, the parts of the Examples are based on mass.

[0311] Production Example of Toner Particles 1

[0312] Here, an example of producing the toner particles 1 will be described.

[0313] Preparation of resin particle dispersion

[0314] 89.5 parts of styrene, 9.2 parts of butyl acrylate, 1.3 parts of acrylic acid and 3.2 parts of n-dodecyl mercaptan were mixed and dissolved. 1.5 parts of Neogen RK (DKS Co., Ltd.) in an aqueous solution in 150 parts of ion exchange water were added and dispersed. Then it was gently stirred for 10 minutes, while adding 0.3 parts of potassium persulfate in an aqueous solution in 10 parts of ion exchange water. After nitrogen purging, emulsion polymerization was carried out at 70°C for 6 hours. After the polymerization was completed, the reaction solution was cooled to room temperature, and ion exchange water was added to obtain a resin particle dispersion having a median volume reference particle size of 0.2 μm and a solid concentration of 12.5% ​​by mass.

[0315] Preparation of release agent dispersion

[0316] 100 parts of a release agent (behenyl behenate, melting point 72.1° C.) and 15 parts of Neogen RK were mixed with 385 parts of ion-exchanged water and dispersed for about 1 hour using a wet jet mill unit JN100 (Jokoh Co., Ltd.) to obtain a release agent dispersion. The solid concentration of the release agent dispersion was 20% by mass.

[0317] Preparation of colorant dispersion

[0318] 100 parts of carbon black as a colorant "Nipex35 (Orion Engineered Carbons)" and 15 parts of Neogen RK were mixed with 885 parts of ion-exchanged water and dispersed in a wet jet mill unit JN100 for about 1 hour to obtain a colorant dispersion.

[0319] Preparation of toner particles

[0320] 265 parts of the resin particle dispersion, 10 parts of the release agent dispersion and 10 parts of the colorant dispersion were dispersed with a homogenizer (Ultra-Turrax T50, IKA). The temperature in the container was adjusted to 30°C under stirring, and 1 mol / L hydrochloric acid was added to adjust the pH to 5.0. After leaving it for 3 minutes, the temperature began to rise, and the temperature rose to 50°C, thereby generating aggregated particles.

[0321] The particle size of aggregated particles was measured under these conditions using a "Multisizer(R) 3 Coulter Counter" (Beckman Coulter, Inc.) Once the weight average particle size reached 6.2 μm, a 1 mol / L sodium hydroxide aqueous solution was added to adjust the pH to 8 and stop particle growth.

[0322] The temperature was then raised to 95° C. to fuse and spheroidize the aggregated particles. The temperature was lowered when the average circularity reached 0.980, and the temperature was lowered to 30° C. to obtain a toner particle dispersion 1.

[0323] Hydrochloric acid was added to adjust the pH of the obtained toner particle dispersion 1 to 1.5 or less, and the dispersion was stirred for 1 hour, allowed to stand, and then subjected to solid-liquid separation in a pressure filter to obtain a toner filter cake. This was slurried with ion exchange water, redispersed, and subjected to solid-liquid separation in the previous filter unit. Reslurrying and solid-liquid separation were repeated until the conductivity of the filtrate was 5.0 μS / cm or less, and finally a solid-liquid separated toner filter cake was obtained.

[0324] The obtained toner cake was dried with a flash dryer (air dryer) (Seishin Enterprise Co., Ltd.). The drying conditions were a blast temperature of 90° C., a dryer outlet temperature of 40° C., and the supply rate of the toner cake was adjusted according to the moisture content of the toner cake so that the outlet temperature would not deviate from 40° C. Using the Coanda effect, the fine powder and the coarse powder were shredded by a multi-stage classifier to obtain toner particles 1. Table 1 shows various physical properties.

[0325] Production Example of Toner Particles 2

[0326] Toner Particles 2 were obtained in the same manner as in the Production Example of Toner Particles 1 except that the particle growth stop time in the generation step of aggregated particles in the Production Example of Toner Particles 1 was changed. Table 1 shows various physical properties.

[0327] Production Example of Toner Particles 3

[0328] Toner Particles 3 were obtained in the same manner as in Production Example of Toner Particles 1, except that paraffin wax (melting point: 75.4°C) was used instead of behenyl behenate (melting point: 72.1°C) in the preparation of the release agent dispersion in Production Example of Toner Particles 1. Table 1 shows various physical properties.

[0329] [Table 1]

[0330]

[0331] Production of fatty acid metal salt fine particles A1

[0332] A receiving container equipped with a stirrer was prepared, and the stirrer was rotated at 350 rpm. 500 parts of a 0.5 mass % sodium stearate aqueous solution were placed in the receiving container, and the liquid temperature was adjusted to 85° C. Then 525 parts of a 0.2 mass % zinc sulfate aqueous solution were dripped into the receiving container over the course of 15 minutes. After all additions were completed, it was cured at the same temperature as the reaction for 10 minutes, and the reaction was terminated.

[0333] The fatty acid metal salt slurry thus obtained was filtered and washed. The washed fatty acid metal salt filter cake obtained was crushed and dried at 105°C using a continuous instantaneous air dryer. It was then ground using a Nano Grinding Mill NJ-300 (Sunrex Industry Co., Ltd.) at 6.0 m 3 / min air flow rate at a processing speed of 80kg / h. It was re-pulped and fine particles and coarse particles were removed by a wet centrifuge. Then it was dried at 80°C by a continuous instantaneous air dryer to obtain dry fatty acid metal salt fine particles A1.

[0334] The volume-based median diameter (D50s) of the obtained fatty acid metal salt fine particles A1 was 0.45 μm, and the span value B was 0.92. Table 2 shows the physical properties of the fatty acid metal salt fine particles A1.

[0335] Production of fatty acid metal salt fine particles A2

[0336] In the production of fatty acid metal salt fine particles A1, the 0.5 mass % sodium stearate aqueous solution was replaced with a 1.0 mass % sodium stearate aqueous solution, and the 0.2 mass % zinc sulfate aqueous solution was replaced with a 0.7 mass % calcium chloride aqueous solution. The reaction was terminated by 5-min aging. In addition, the pulverization conditions were changed to an air volume of 5.0 m 3 / min, and after pulverization, fine powder and coarse powder were removed with an air type classifier to obtain fatty acid metal salt fine particles A2.

[0337] The volume-based median diameter (D50s) of the obtained fatty acid metal salt fine particles A2 was 0.58 μm, and the span value was 1.73. Table 2 shows the physical properties of the fatty acid metal salt fine particles A2.

[0338] Production of fatty acid metal salt fine particles A3

[0339] Fatty acid metal salt fine particles A3 were obtained in the same manner as the production of fatty acid metal salt fine particles A1, except that the 0.2 mass % zinc sulfate aqueous solution was replaced with a 0.3 mass % lithium chloride aqueous solution. The volume-based median diameter (D50s) of the obtained fatty acid metal salt particles A3 was 0.33 μm, and the span value B was 0.85. Table 2 shows the physical properties of fatty acid metal salt fine particles A3.

[0340] Production of fatty acid metal salt fine particles A4

[0341] In the production of fatty acid metal salt fine particles A1, the 0.5 mass % sodium stearate aqueous solution was replaced with a 0.5 mass % sodium laurate aqueous solution, and the pulverization conditions were changed to 10.0 m 3The pulverization step was performed 3 times. The volume-based median diameter (D50s) of the obtained fatty acid metal salt particles A4 was 0.18 μm, and the span value B was 1.34. Table 2 shows the physical properties of the fatty acid metal salt fine particles A4.

[0342] Production of fatty acid metal salt fine particles A5

[0343] In the production of fatty acid metal salt fine particles A1, 0.05 mass % sodium stearate aqueous solution was used instead of 0.5 mass % sodium stearate aqueous solution, and 0.02 mass % zinc sulfate aqueous solution was used instead of 0.2 mass % zinc sulfate aqueous solution. The pulverization conditions were changed to 10.0 m 3 The air flow rate was 0.0447 W / min, and the pulverization step was performed 3 times. Thereafter, coarse particles were removed by a sieve without going through a classification step, thereby obtaining fatty acid metal salt fine particles A5.

[0344] The volume-based median diameter (D50s) of the obtained fatty acid metal fine particles A5 was 0.12 μm, and the span value B was 1.05. Table 2 shows the physical properties of the fatty acid metal salt fine particles A5.

[0345] Production of fatty acid metal salt fine particles A6

[0346] As fatty acid metal salt fine particles A6, commercially available zinc stearate (SZ2000, manufactured by Sakai Chemical Industry Co., Ltd.) was used. The volume-based median diameter (D50s) was 5.30 μm, and the span value was 1.84. Table 2 shows the physical properties of fatty acid metal salt fine particles A6.

[0347] [Table 2]

[0348]

[0349] Production Example of Fine Particles B1

[0350] Ilmenite ore containing 50% by mass of TiO2 equivalent is dried at 150°C for 3 hours and then dissolved by adding sulfuric acid to obtain an aqueous solution of TiOSO4. After concentrating the obtained aqueous solution, 10 parts of titanium oxide sol having rutile crystals are added as seeds, and then hydrolyzed at 170°C to obtain a slurry of TiO(OH)2 containing impurities. The slurry is repeatedly washed at pH 5 to 6, and sulfuric acid, FeSO4 and impurities are fully removed to obtain a slurry of high-purity metatitanic acid [TiO(OH)2].

[0351] After the slurry was filtered, 0.5 parts of lithium carbonate (Li2CO3) was added, and the mixture was calcined at 250°C for 3 hours. Then, depolymerization treatment was repeated by a jet mill to obtain fine titanium oxide particles with rutile crystals. A total of 5 parts of isobutyltrimethoxysilane as a surface treatment agent was added dropwise, mixed and reacted with 100 parts of fine titanium oxide particles, and the obtained fine titanium oxide particles were dispersed in ethanol and stirred. After drying, the mixture was heat treated at 170°C for 3 hours, and depolymerization treatment was repeated with a jet mill until the titanium oxide aggregates disappeared, thereby obtaining fine particles B1 as fine titanium oxide particles. Table 3 shows physical properties.

[0352] Production Example of Fine Particles B2

[0353] Fine Particle B2 as titanium oxide fine particle was obtained in the same manner as Fine Particle B1 except that in the production example of Fine Particle B1, the calcination temperature was 240° C. and the amount of isobutyltrimethoxysilane as the surface treatment agent was changed to 15 parts. Table 3 shows the physical properties.

[0354] Production Example of Fine Particles B3

[0355] Fine Particle B3 as a titanium oxide fine particle was obtained in the same manner as the fine particle B1 except that the calcination temperature in the production example of the fine particle B1 was changed to 260° C. Table 3 shows the physical properties.

[0356] Production Example of Fine Particles B4

[0357] After obtaining metatitanic acid by the sulfuric acid method, it is subjected to iron removal bleaching treatment, sodium hydroxide aqueous solution is added to adjust the pH to 9.0, desulfurization treatment is performed, and then it is neutralized to pH 5.8 with hydrochloric acid, followed by filtration and water washing. Water is added to the washed filter cake to form a slurry of 1.85 mol / L in terms of TiO2, and then hydrochloric acid is added to adjust the pH to 10, followed by deflocculation.

[0358] The desulfurized and deflocculated metatitanic acid was collected in an amount of 1.88 mol in terms of TiO2 and charged into a 3 L reaction vessel. A total of 2.16 mol of strontium chloride aqueous solution was added to the deflocculated metatitanic acid slurry to make the Sr / Ti (molar ratio) 1.15, and the concentration of TiO2 was adjusted to 1.039 mol / L.

[0359] Next, the mixture was heated to 90°C, stirred and mixed, and 440 mL of a 10 mol / L sodium hydroxide aqueous solution was added over 45 min. After that, stirring was continued at 95°C for 1 hour to complete the reaction. The reaction slurry was cooled to 50°C, hydrochloric acid was added until the pH reached 5.0, and stirring was continued for 1 hour. The precipitate obtained was washed by decantation.

[0360] The slurry containing the precipitate was adjusted to 40° C., and the pH was adjusted to 2.5 by adding hydrochloric acid. Then, 4.0% by mass of n-octyltriethoxysilane was added relative to the solid content, and the mixture was stirred for 10 hours.

[0361] The filter cake obtained by adjusting pH to 6.5, adding 5 mol / L sodium hydroxide solution and continuing stirring for 1 hour, followed by filtration and washing was dried in air at 120° C. for 8 hours to obtain fine particles B4 as strontium titanate fine particles. Table 3 shows physical properties.

[0362] Production Example of Fine Particles B5

[0363] At 50Nm 3 / h to supply oxygen to the combustion chamber at 2Nm 3 Argon gas is supplied to the combustion chamber at 1000 rpm to form an aluminum powder ignition zone. Next, aluminum powder (average particle size: about 45 μm, supply amount: 20 kg / h) is supplied to the reaction furnace through the combustion chamber together with nitrogen gas (supply amount: 3.5 kg / h) from the aluminum powder supply device.

[0364] Alumina particles were obtained by oxidizing aluminum powder in a reaction furnace. The aluminum oxide particles obtained after passing through the reaction furnace were classified to remove fine powder and coarse powder, thereby obtaining aluminum oxide fine particles B5. Table 3 shows the physical properties.

[0365] Production Example of Fine Particles B6

[0366] Fine Particle B6 as strontium titanate fine particles was obtained in the same manner as the fine particle B4 except that 6.0 mass % of n-octyltriethoxysilane was added relative to the solid content. Table 3 shows the physical properties.

[0367] [Table 3]

[0368]

[0369] Fine particles C1 to C2

[0370] The fine particles C shown in Table 4 were used.

[0371] [Table 4]

[0372] Fine particles C Material Number average particle size of primary particles (nm) Fine particles C1 Silicon dioxide 10 Fine particles C2 Silicon dioxide 55

[0373] Production Example of Toner 1

[0374] As a first step, the toner particles 1 and the fine particles B1 are mixed using an FM mixer (FM10C model, manufactured by Nippon Coke Industry Co., Ltd.).

[0375] While the water temperature of the jacket of the FM mixer was kept stable at 50°C ± 1°C, 100 parts of toner particles 1 and 1.00 parts of fine particles B1 were charged into the mixer. Mixing was started with the peripheral speed of the rotating blade at 38 m / sec and continued for 7 minutes while controlling the water temperature and flow rate of the jacket so that the temperature in the water tank was kept stable at 50°C ± 1°C, thereby obtaining a mixture of toner particles 1 and fine particles B1.

[0376] Subsequently, as a second step, fine particles A1 and fine particles C1 were added to the mixture of toner particles 1 and fine particles B1 using an FM mixer (FM10C model, manufactured by Nippon Coke Industry Co., Ltd.). While the water temperature of the jacket of the FM mixer was stabilized at 25°C±1°C, 0.20 parts of fine particles A1 and 0.80 parts of fine particles C1 were added to 100 parts of toner particles 1. Mixing was started with a circumferential speed of 20 m / sec for 5 minutes while controlling the water temperature and flow rate of the jacket so that the temperature in the water tank was stabilized at 25°C±1°C. After mixing, the mixture was sieved through a mesh having an aperture of 75 μm, thereby obtaining toner 1.

[0377] Tables 5-1 and 5-2 show the production conditions of Toner 1, and Table 6 shows various physical properties of Toner 1.

[0378] [Table 5-1]

[0379]

[0380] In the table, "C." indicates comparison.

[0381] [Table 5-2]

[0382]

[0383] In the table, "C." stands for comparison and "T." stands for temperature.

[0384] Production Examples of Toners 2 to 29 and Comparative Toners 1 to 12

[0385] Toners 2 to 29 and Comparative Toners 1 to 12 were obtained in the same manner as in the manufacturing example of Toner 1 except that the toner particles added in the first, second and third steps, the number of parts of fine particles A to C and the mixing conditions shown in Tables 5-1 and 5-2 were changed. Table 6 shows the physical properties.

[0386] [Table 6]

[0387]

[0388] In the table, "C." means comparison, "amount D" means "amount D of fine particles A (mass %)", "coverage E" means "coverage E of fine particles A (%)", "D index" means "dispersion index of fine particles B" and "FG" means "fixation rate G of fine particles A (%)".

[0389] Production Example of Electrophotographic Photosensitive Member

[0390] An aluminum cylinder (JIS A 3003, aluminum alloy) having a diameter of 24 mm and a length of 257.5 mm was used as a support (conductive support).

[0391] Next, 214 parts of titanium oxide (TiO2) particles (average primary particle size 230 nm) covered with oxygen-deficient tin oxide (SnO2) as metal oxide particles, 132 parts of phenol resin (monomer / oligomer of phenol resin) as a binder material (trade name: PLYOFEN J-325, manufactured by Dainippon Ink and Chemicals, Inc., resin solid content: 60% by mass) and 98 parts of 1-methoxy-2-propanol as a solvent were placed in a sand mill using 450 parts of glass beads having a diameter of 0.8 mm, and dispersed under the conditions of a rotation speed of 2000 rpm, a dispersion treatment time of 4.5 hours and a cooling water setting temperature of 18° C. to obtain a dispersion liquid. The glass beads were removed from the dispersion liquid with a mesh (aperture: 150 μm).

[0392] Silicone resin particles (trade name: TOSPEARL 120, manufactured by Momentive Performance Materials Co., Ltd., average particle diameter 2 μm) as a surface roughening material were added to the dispersion to obtain 10% by mass relative to the total mass of the metal oxide particles and the binder material in the dispersion after removing the glass beads. Silicone oil (trade name: SH28PA, manufactured by Dow Corning Toray Co., Ltd.) as a leveling agent was added to the dispersion to obtain 0.01% by mass relative to the total mass of the metal oxide particles and the binder material in the dispersion.

[0393] Next, a mixed solvent of methanol and 1-methoxy-2-propanol (mass ratio 1:1) was added to the dispersion so that the metal oxide particles, binder material and surface roughening material (i.e., the mass of the solid component) in the dispersion were 67 mass % relative to the mass of the dispersion, and the mixture was stirred to prepare a conductive layer coating solution. The conductive layer coating solution was dip-coated on the support and heated at 150°C for 30 minutes to form a conductive layer with a thickness of 30.0 μm.

[0394] Formation of base coat

[0395] A total of 4 parts of an electron transport material (E), 5.5 parts of a blocked isocyanate (trade name: DURANATE SBN-70D, manufactured by Asahi Kasei Chemicals Corporation), 0.3 parts of a polyvinyl butyral resin (S-LEC KS-5Z, manufactured by Sekisui Chemical Co., Ltd.), and 0.05 parts of zinc (II) hexanoate (manufactured by Mitsui Chemicals, Inc.) as a catalyst were dissolved in a mixed solvent of 50 parts of tetrahydrofuran and 50 parts of 1-methoxy-2-propanol to prepare an undercoat coating solution. The undercoat coating solution was dip-coated on the conductive layer and heated at 170°C for 30 minutes to form an undercoat layer having a thickness of 0.7 μm.

[0396]

[0397] Formation of charge generation layer

[0398] Next, 10 parts of crystalline hydroxygallium phthalocyanine having peaks at 7.5° and 28.4° in a graph obtained from CuKα characteristic X-ray diffraction and 5 parts of polyvinyl butyral resin (trade name: S-LEC BX-1, manufactured by Sekisui Chemical Co., Ltd.) were added to 200 parts of cyclohexanone and dispersed in a sand mill using glass beads having a diameter of 0.9 mm for 6 hours. To this end, 150 parts of cyclohexanone and 350 parts of ethyl acetate were further added for dilution to obtain a charge generating layer coating solution.

[0399] The obtained coating liquid was dip-coated on the undercoat layer and dried at 95° C. for 10 minutes to form a charge generation layer having a thickness of 0.20 μm. X-ray diffraction measurement was performed under the following conditions.

[0400] Powder X-ray diffraction measurement

[0401] Measuring device: X-ray diffractometer RINT-TTRII, manufactured by Rigaku Denki Co., Ltd.

[0402] X-ray tube: Cu

[0403] Tube voltage: 50KV

[0404] Tube current: 300mA

[0405] Scanning mode: 2θ / θ scanning

[0406] Scanning speed: 4.0° / min

[0407] Sampling interval: 0.02°

[0408] Starting angle (2θ): 5.0°

[0409] Stop angle (2θ): 40.0°

[0410] Accessories: Standard sample table

[0411] Filter: Not used

[0412] Incident Monochrome: Use

[0413] Counter Monochromator: Not used

[0414] Diverging slits: Open

[0415] Divergence vertical limiting slit: 10.00mm

[0416] Scattering slit: Open

[0417] Light receiving slit: Open

[0418] Flat-plate monochromator: Use

[0419] Counter: Scintillation counter

[0420] Formation of charge transport layer

[0421] Next, 6 parts of a compound represented by the following formula (C-1) (charge transport substance (hole transport compound)), 3 parts of a compound represented by the following formula (C-2) (charge transport substance (hole transport compound)), 1 part of a compound represented by the following formula (C-3) (charge transport substance (hole transport compound)), 10 parts of polycarbonate (trade name: Iupilon Z400, manufactured by Mitsubishi Engineering-Plastics Corporation) and 0.02 parts of a polycarbonate resin having copolymerization units of (C-4) and (C-5) (x / y=9 / 1: Mw=20000) were dissolved in a mixed solvent including 25 parts of o-xylene, 25 parts of methyl benzoate and 25 parts of dimethoxymethane to prepare a charge transport layer coating liquid. The charge transport layer coating liquid was dip-coated on the charge generating layer to form a coating film, which was then dried at 120° C. for 30 min to form a charge transport layer having a thickness of 12 μm.

[0422]

[0423] Formation of protective layer

[0424] Next, 10 parts of the compound represented by the following formula (O-1) and 10 parts of the compound represented by the following formula (O-2) were mixed with 50 parts of 1-propanol and 25 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane (trade name: ZEOROLA H, manufactured by Nippon Zeon Co., Ltd.) and stirred.

[0425] Thereafter, the solution was filtered through a polyflon filter (trade name: PF-020, manufactured by Advantec Toyo Kaisha, Ltd.), thereby preparing a protective layer coating solution.

[0426]

[0427] The protective layer coating solution was dip-coated onto the charge transport layer to form a coating film, and the obtained coating film was dried at 50° C. for 6 minutes. Thereafter, the coating film was irradiated with an electron beam for 5.0 seconds in a nitrogen atmosphere while the support (irradiation target) was rotated at a speed of 200 rpm under the conditions of an accelerating voltage of 70 kV and a beam current of 5.0 mA. The absorbed dose of the electron beam measured at this time was 15 kGy.

[0428] Thereafter, in a nitrogen atmosphere, the temperature of the coating film was raised from 25°C to 117°C within 30 seconds to heat the coating film. The oxygen concentration from electron beam irradiation to the subsequent heat treatment was 15 ppm or less. Next, the coating film was naturally cooled in the atmosphere until the temperature of the coating film reached 25°C, and then heated for 30 minutes under the condition that the coating film temperature reached 105°C, thereby forming a protective layer with a thickness of 3 μm. Thus, an electrophotographic photosensitive member having a protective layer was manufactured.

[0429] Thus, a cylindrical (drum-shaped) electrophotographic photosensitive member 1 having the support, the undercoat layer, the charge generating layer, the charge transporting layer, and the protective layer in this order is produced.

[0430] Example 1

[0431] A modified version of a commercially available laser beam printer LBP9950Ci manufactured by Canon Inc. was used. The modifications included setting the rotation speed of the developing roller to twice the circumferential speed of the drum and changing the process speed to 330 mm / sec by changing the gears and software of the evaluation device body. The toner contained in the LBP9950Ci toner cartridge was drawn out, the inside thereof was cleaned with a blower, and then 180 g of the toner to be evaluated was loaded. The electrophotographic photosensitive member was removed, and an electrophotographic photosensitive member 1 was newly set. Since a hard photosensitive member having a hardened surface protective layer was used, it was difficult to scrape off nitrogen oxides, and strict conditions for image smear were achieved. Then, the toner cartridge was placed in a low temperature and low humidity environment of L / L (10°C / 15% RH) and a high temperature and high humidity environment of H / H (30°C / 80% RH) for 5 days.

[0432] A toner cartridge allowed to stand in a low temperature, low humidity environment L / L for 5 days was installed on the cyan workstation of the LBP9950Ci until 20,000 images were printed with a print percentage of 1.0%, and the retransfer (after durability), development streaks, and image density uniformity (L / L) of the initial output and the 20,000th output were evaluated.

[0433] Evaluation of retransfer

[0434] At the initial stage and after the 20,000th print, a cartridge without toner was placed in the black station and a cartridge containing the toner to be evaluated was placed in the cyan station. The developing voltage was then adjusted so that the toner load was 0.6 mg / cm 2 , and output a fully solid image.

[0435] Next, the toner on the photosensitive member of the cartridge re-transferred to the black station was removed by sticking with Mylar tape. Thereafter, the tape and the unsticked tape were stuck to LETTER-sized XEROX 4200 paper (manufactured by XEROX Corporation, 75 g / m 2 The reflectance (%) of each tape was measured using "REFLECTOMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.).

[0436] Then, the value (retransfer) (%) obtained by subtracting the reflectance (%) of the attached tape from the reflectance (%) of the unattached tape was used for evaluation. The smaller the value of retransfer, the more retransfer was suppressed. C and above were determined to be satisfactory.

[0437] A: The retransfer was less than 2.0%.

[0438] B: The retransfer is 2.0% or more and less than 5.0%.

[0439] C: The retransfer is 5.0% or more and less than 10.0%.

[0440] D: Retransfer 10.0% or more.

[0441] Evaluation of Development Streaks

[0442] After printing 20,000 sheets, a halftone image was printed. The printed halftone image was evaluated according to the following criteria. B and above were determined to be satisfactory.

[0443] A: The number of stripes on the halftone image is 0 or 1.

[0444] B: The number of stripes on the halftone image is 2 to 4.

[0445] C: The number of streaks on the halftone image is 5 or more.

[0446] Evaluation of image density uniformity

[0447] The evaluation of image density uniformity was conducted in a low temperature and low humidity environment (temperature: 15.0°C, relative humidity: 10%), which is considered to be more severe in retransfer because the retransfer effect is significant. Rough paper FOXRIVER BOND paper (110 g / m 2 ).

[0448] In the image density evaluation, an image with a top edge of 5 mm, left and right edges of 5 mm, and a solid black streak image of 5 mm × 5 mm was output at the following 9 positions in total after printing the first and 20,000th sheets in the long-term durability test: 3 positions at intervals of 30 mm in 3 placement directions (left, right and center).

[0449] The image density of nine solid black streak image parts of the image is measured, and the difference between the maximum and minimum values ​​of all concentrations is obtained. Use Macbeth densitometer (manufactured by MACBETH) to measure image density using SPI filter. The smaller the numerical difference between the maximum and minimum values, the better the image density uniformity. B and above are determined to be satisfactory.

[0450] A: The difference between the maximum value and the minimum value of the image density is 0.05 or less.

[0451] B: The difference between the maximum value and the minimum value of the image density is 0.06 to 0.10.

[0452] C: The difference between the maximum value and the minimum value of the image density is 0.11 or more.

[0453] Evaluation of Image Smear

[0454] A toner cartridge left in a high temperature and high humidity environment for 5 days was mounted on the cyan station of the LBP9500C, and an A4 image of 1-dot 2-space horizontal ruled lines was intermittently printed 20,000 times in the durability mode.

[0455] After that, the box was placed in an H / H environment for 72 hours, and an A4 image of horizontal grid lines with 1 point and 2 intervals was output. The reduction rate (%) of the grid line width after standing for 72 hours relative to the image before standing for 72 hours was evaluated based on the following criteria. The thickness of the grid lines of the image is the average value of the thickness of multiple grid lines in one image. The reduction rate (%) of the grid line width is calculated by the following formula. C and above are determined to be satisfactory.

[0456] Ruled line width reduction rate (%) = {[(ruled line thickness of image before allowing image placement) - (ruled line thickness of image after allowing image placement)] / (ruled line thickness of image before allowing image placement)} × 100

[0457] A: The reduction rate of the grid width is less than 10%.

[0458] B: The reduction rate of the ruled line width is 10% or more and less than 25%.

[0459] C: The ruled line width reduction rate is 25% or more and less than 40%.

[0460] D: The reduction rate of the ruled line width is 40% or more.

[0461] [Table 7]

[0462]

[0463] In the table, "C." indicates comparison.

[0464] Examples 2 to 29, Comparative Examples 1 to 12

[0465] Evaluation was performed in the same manner as in Example 1. Table 7 shows the evaluation results.

[0466] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising toner particles, wherein the toner particles contain a binder resin, wherein: Fine particles A and fine particles B are present on the surface of the toner particles; The fine particles A are fatty acid metal salts; The amount of the fine particles A is 0.02 parts by mass to 1.80 parts by mass relative to 100 parts by mass of the toner particles; The fixing rate of the fine particles A to the toner particles is 0.0 to 8.0%; The volume resistivity of the fine particles B is 5.0×10Ωm to 1.0×10 8 Ωm; When the average theoretical surface area obtained from the number average particle diameter, particle size distribution and true density of the toner particles measured by a Coulter counter is expressed in m 2 / g is represented by C, The amount of the fine particles A is represented by D in parts by mass relative to 100 parts by mass of the toner particles, and When the coverage of the surface of the toner particle by the fine particles A is represented by E in %, Satisfies the following equations (1) and (2): 0.03≤D / C≤1.50 (1), E / (D / C)≤50.0 (2); The amount of the fine particles B is 0.10 parts by mass to 3.00 parts by mass relative to 100 parts by mass of the toner particles; and In observation of the cross section of the colorant by a transmission electron microscope, in the total area occupied by the fine particles B existing in the cross section of one particle of the colorant, a ratio F of the area occupied by a part of the fine particles B in which the length of the portion of each fine particle B in contact with the colorant particle is more than 50% of the circumference of each fine particle B and which exists in the vicinity of the surface from the outline of the cross section of one particle of the colorant to the inner side of 30 nm toward the center of gravity of the cross section is more than 50 area %.

2. The toner according to claim 1, wherein The fixing rate of the fine particles A to the toner particles is represented by G in %, The relationship between G and the area ratio F satisfies the following formula (3): 2.0≤(100-G) / (100-F)≤8.0 (3). 3 . The toner according to claim 1 , wherein a dispersion evaluation index of the fine particles B to the surface of the toner is 0.4 or less.

4. The toner according to claim 1 or 2, wherein Fine particles C are present on the surface of the toner particles; The fine particles C are silicon dioxide fine particles; and In observation of the cross section of the colorant by a transmission electron microscope, in the total area occupied by the fine particles C existing in the cross section of one particle of the colorant, the ratio of the area occupied by a part of the fine particles C in which the length of the portion of each fine particle C in contact with the colorant particle is more than 50% of the circumference of each fine particle C and which exists in the vicinity of the surface from the outline of the cross section of one particle of the colorant to the inner side of 30 nm toward the center of gravity of the cross section is less than 40 area %. 5 . The toner according to claim 1 , wherein a volume-based median diameter of the fine particles A is from 0.15 μm to 3.00 μm. 6 . The toner according to claim 1 , wherein the fine particles A are fatty acid metal salts of a divalent or higher polyvalent metal and a fatty acid having 8 to 28 carbon atoms. 7 . The toner according to claim 6 , wherein the divalent or higher-valent polyvalent metal includes zinc. 8 . The toner according to claim 1 , wherein the number average particle diameter of primary particles of the fine particles B is from 5 nm to 50 nm. 9 . The toner according to claim 1 , wherein the toner particles include an ester wax having a melting point of 60° C. to 90° C.

10. The toner according to claim 1 or 2, wherein Fine particles C are present on the surfaces of the toner particles; and The fine particles C are silica fine particles having a primary particle number average particle diameter of 5 nm to 50 nm.

11. The toner according to claim 1 or 2, wherein The fine particles B are at least one type of particles selected from the group consisting of titanium oxide fine particles and strontium titanate fine particles.